Modulation of Cellular Calcium Adenosine Triphosphatase in Tissues of Rats Fed with Protein-Deficient Diet Fortified with Moringa oleifera Leaves - Ismaila Olanrewaju Nurain,; Bamisaye F Abraham,; Ajani O Emmanuel, (International Journal of Phytomedicine, 2013)
Calcium Adenosine Triphosphatase is a ubiquitous enzyme and key protein for the maintenance of calcium homeostasis in various cellular compartments. Moringa leave has been reported to be a very good source of dietary protein as well as pool of minerals. So far the effect of varying dietary protein on the activities of Ca2+ pump across cell membranes is yet to be fully explained. In this study, the effects of protein deficiency on Ca2+-ATPase activities were investigated. Twenty four Wistar rats (average weight 119±0.3 g) randomised into four groups of six (6) rats each were used for the study. Group A rats were treated with normal animal diet, group B were placed on protein-deficient diet, Group C were treated with protein deficient diet fortified with fish while Group D were administered with protein deficient diet fortified with Moringa oleifera leaves powder. They were maintained on respective diets for 6 weeks then sacrificed. The skeletal muscle, brain and liver were removed and homogenised. Vanadate is a known cellular Ca2+-ATPase inhibitor and was used to confirm the sensitivity of the enzyme in the homogenate. The protein concentration in each formulated diet was determined to be 9.71%, 2.19%, 23.92% and 31.54% for group A, B, C and D respectively. The enzyme’s activities were highest in group D and lowest in Group B. In the same line, the activities were also highest in the skeletal muscle and lowest in the liver of all the groups. The Km (ATP) and Vmax of the enzyme in all the studied organs were lowest in group D and highest in group B. The results indicate that protein deficiency reduces the activities of Ca2+-ATPase in the entire tissues’ cells and that M. oleifera leave powder is a better activator for the enzyme and therefore a good modulator of Ca2+-ATPase activities